2021
DOI: 10.1093/beheco/arab102
|View full text |Cite
|
Sign up to set email alerts
|

Population differences in the effect of context on personality in an invasive lizard

Abstract: Within populations, individuals often differ consistently in their average level of behavior (i.e., animal personality), as well as their response to environmental change (i.e., behavioral plasticity). Thus, changes in environmental conditions might be expected to mediate the structure of animal personality traits. However, it is currently not well understood how personality traits change in response to environmental conditions, and whether this effect is consistent across multiple populations within the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…As Lampropholis delicata is a social species, skinks were housed in groups of up to seven individuals in plastic containers (300 × 370 mm) within temperature-controlled rooms (13:11 h light/dark cycle, maintained at 22.5 ± 1 °C), in line with established protocols 63 , 64 . Skinks from each population were randomly assigned to housing containers, with approximately 7 separate housing containers used for each population (i.e., ~98 housing containers total).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Lampropholis delicata is a social species, skinks were housed in groups of up to seven individuals in plastic containers (300 × 370 mm) within temperature-controlled rooms (13:11 h light/dark cycle, maintained at 22.5 ± 1 °C), in line with established protocols 63 , 64 . Skinks from each population were randomly assigned to housing containers, with approximately 7 separate housing containers used for each population (i.e., ~98 housing containers total).…”
Section: Methodsmentioning
confidence: 99%
“…This created a thermal gradient (22–32 °C) that allowed all skinks to thermoregulate from 0800 to 1700 h. Similarly, UV lighting was provided above containers from 0800–1800 h. Skinks were fed a diet of crickets ( Acheta domesticus ) dusted in a vitamin supplement (Reptivite), three times a week, and water was made available ad libitum. Skinks were acclimated to these standardized laboratory conditions for at least 1 week before experiments, in line with previously established protocols 43 , 64 .…”
Section: Methodsmentioning
confidence: 99%
“…While lizards in the current experiment were previously used in a study comparing population differences in skink activity rates when in groups (i.e. no individual trials), none of the data presented here were previously reported in Brand et al ( 2021a ). Instead, we chose to focus on shelter use across varying social conditions in the present study as we were interested in the consistency of risk-taking behaviour when measured during individual and group assays.…”
Section: Methodsmentioning
confidence: 94%
“…For example, some individuals tend to be more prone to risk-taking or are more active and exploratory than other conspecifics in the population (e.g. Jolles et al 2019 ; Michelangeli et al 2019 ; Brand et al 2021a , b ). These ‘personality traits’ or ‘behavioural types’ are typically heritable (Dingemanse et al 2002 ; Dochtermann et al 2015 ), can affect organismal fitness (Moirón et al 2019 ; Munson et al 2020 ), as well as species interactions and biological invasions (Chapple et al 2012 ; Sih et al 2012 ; Wolf and Weissing 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Brand et al (2021a) , all models were run on four chains using relatively uninformative, default priors for a total of 5000 iterations, with a warm-up of 1000, and a thinning interval of 2. Model convergence was verified with sufficient mixing of trace plots, with all values = 1.…”
Section: Methodsmentioning
confidence: 99%